Pelatihan Ecoprint Teknik Steam Bagi Masyarakat Non Pengrajin Tempe di Sanan Malang - Lisa Sidyawati; sumarwahyudi; E. Wara Suprihatin Dyah Pratamawati; Ike Ratnawati (Universitas Medan Area, 2023)
Kampung Sanan Malang has a population of 481 households, 262 of which have opened a business to produce tempeh and tempeh chips. RW15 Sanan's Profile Book states that the turnover of money from the industry reaches nearly forty billion rupiahs per month. However, there are still around a hundred families whose welfare still needs to be improved. Welfare distribution efforts include skills training to open up new business opportunities. One of the work programs of RW 15 Sanan is conducting coaching by involving outside parties to assist, and skills training to reduce unemployment and improve the standard of living of non-tempe craftsmen. One of the travel awareness group (Pokdawis) businesses that has been running well is the educational tourism business based in the Sanan thematic village. This business led to the idea to open a new business, namely the production of eco-print-based souvenirs. Based on these problems, eco-print training was carried out using the steam technique.